Leveraging community participation through health committees to achieve health rights : the role of power - Hasson, Marion (Department of Public Health and Family Medicine, 2016)
The concept of health committees has been promoted as an effective mechanism for assisting communities to realize their health rights. These committees tend to be formal structures made up of representatives from local government, health facilities and communities. Much of the attention has focused on identifying strategies and interventions to strengthen health committees as vehicles for achieving the right to health and the focus has been on educating, raising awareness, training and policy advocacy. However, it is important to understand what participation looks like on the ground and to take in to account the day-to-day challenges and obstacles that health committees as a vehicle for community participation; interacting with stakeholders; and getting support from health facility managers and staff. These factors impact on the health committees 'ability to facilitate and support community participation, yet they are driven by power dynamics and human interactions and relationships. Little attention has been paid to these dynamics, which play an important role in meaningful community participation at grassroots. The Power Cube framework was used to explore the multiple dimensions of power that hinder or enable the health committees' ability to support the community to realize their right to health. The Power Cube framework allowed for an investigation of how power dynamics are perceived by a particular group, as well as providing for the comparison of different social, economic and political context. It enabled a comparison with different contexts where there are policies for supporting the community participation in health but implementation has been difficult it in practice.